Cultural Heritage as a element attractive Tourist destination (on the example of the East Kazakhstan region) (Journal of Geography and Environmental Management, 2016)
The article deals with cultural and historical monuments as elements of the East Kazakhstan region in the tourism sector. Based on the results of a comprehensive study of zoning in the degree of attractivenessof natural landscapes and the degree of saturation of the socio-economic tourist and recreational resources offered conceptual directions of development of promising types of tourism area. Based on theassessment of tourist destinations determined the degree of the potential field of cultural and historical monuments. Attractive to domestic and foreign visitors are Sarykol petroglyphs Moinak, memorial complex “Abai – Shakar”, which act as the attractive elements of a tourist destination and an analysis of the factors hindering the development of tourism sector in this area.
Keywords: Tourist destination; Cultural and historical monuments; Tourist and Recreational zoning; Attractive Factors; etc.; туристік аудандастыру; тежеуіш факторлар және т.б.